Yurchenko I.V. Feature Detection Methods in Image Recognition Problems on Python // International Scientific Conference “Modern Systems of Science and Education in the USA, EU and Postsoviet Countries ‘2021”. Conference Proceedings (February, 2021).– «ISE&E» & SWorld in conjunction with KindleDP Seattle, Washington, USA.– P.25-28. - Yurchenko, Igor Valeryjovych («ISE&E» & SWorld in conjunction with KindleDP Seattle, Washington, USA., 2021)
It is described an implementation of the “Histogram of Oriented Gradients” (HOG) feature detecting algorithm; the construction of classifiers for machine learning problems is considered and Python language tools (Scikit-Learn library) have developed a step-by-step pattern recognition algorithm using the HOG feature detection method and the SVM-classifier; the work of SVM is compared with the naive Bayesian classifier.
None
Keywords: histogram of oriented gradients, pattern recognition algorithm, Scikit-Learn library